Fabricated narrow diameter distribution nanofiber for an air filtration membrane using a double rings slit spinneret. Issue 6 (March 2019) - Wei, Liang; Zhang, Hongnan; Qin, Xiaohong
A needleless electrospinning setup called "Needleless Double Rings Slit Electrospinning" was proposed for the first time. The control pump transports solution to the double rings slits through an insulated infusion tube. High voltage is applied to the metal ring and electric force exceeds the surface tension and viscosity, and multiple jets are spontaneously formed on the top of solution surface. Different spinning process parameters, including solution concentration, applied voltage, collection distance and spinning time, have an influence on nanofiber diameter distribution. The morphology of nanofibers has been observed using scanning electron microscopy. It is worth noting that narrow diameter distribution nanofibers have been fabricated using a novel double rings slit spinneret. Nanofiber diameter distribution has determined the mean pore diameter, pore diameter distribution, filtration efficiency and filtration resistance. The final results show that the pore size and filtration property for nanofiber membranes are significantly related with nanofiber diameter distribution. Narrow diameter nanofibers have contributed to the improvement of filtration properties for nanofiber membranes.